PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERSUMBER ETNOMATEMATIKA DALAM PENENTUAN HARI BAIK PERNIKAHAN MASYARAKAT JAWA - Ayu Anggraini; yulis jamiah; Dede Suratman (Universitas Tanjungpura, 2023)
LKPD which is widely known and used in learning, usually only contains practice questions to measure students abilities and does not relate it to the cultural context. Culture is closely related to students, where culture is related to activities in everyday life. The Ethnomatematics Based Worksheet, Javanese culture is given which can help students understand the concept of sets, hoping to attract students interest. Research hopelly that the community will become more open to the surrounding culture. Research hopelly can also contribute to the field of education, especially as a learning medium in mathematics. This study former a development model with a Research and Development (R&D) in 4D form. The research instruments former were questionnaires, interviews and literature study. The subjects were 9 SMP students who had gone through the material to understand the concept of sets. The Ethnomatematics-based worksheets were appropriate for learning in Pontianak, especially for class VII SMP in learning mathematics on set concept material is showed in the result